A Data Item Selection Mechanism for Mobile Opportunistic Networks. (14th May 2014) - You, Lei; Li, Jianbo; Wei, Changjiang; Xu, Jixing; Dai, Chenqu
The nonexistence of an end-to-end path poses great challenges to directly adapting the traditional routing algorithms for Internet and mobile ad hoc networks (MANETs) to mobile opportunistic networks (MONs). In this paper, we try to improve the routing performance by resorting to an efficient data item selection mechanism that takes the bandwidth and connection duration time into consideration. For the purpose of evaluation, a specific data item selection mechanism for a probability-based routing is devised, which is formally defined as an optimal decision-making problem and solved by the dynamic programming technique. The simulation results show that our data item selection mechanism greatly reduces the number of aborted transmissions thus enhancing the routing performance in aspects of delivery probability, average latency, and overhead ratio.